Mechanism of management of sports movements in conditions of developing fatigue - Gorodnichev, R.; Moisseev, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Management of movements represents a complicated multi-level neuronal system functioning on hierarchical principle (G. Courtine et al,2007). Specific mechanisms of management of complete motor actions of a human depend on the level of skills of the motor response, its difference from natural locomotions, time and amplitude parameters of the performed movement, its particular parameters and other factors. Detection of mechanisms of coordination of sport movements is of considerable interest as their performance is connected with exact time and amplitude parameters, development of great muscle efforts and high speed of working muscle contraction. Methods: 82 athletes-wrestlers (judo) participated in the research aimed at investigation of biomechanical and EMG parameters of skeletal muscles during motor actions of different coordination complexity. Besides, there were studied changes of the structure of a «leg grip» throw in the process of fatigue caused by two kinds of physical activities. The following loadings were applied: 1) technique - performance of techniques within 5 minutes; 2) competitive - 6 competitive fights with a 5-minute interval. Biomechanical parameters and electrical activity were registered by the programme complex Star Trace (Video Motion, 2005) and electromyography «Neuro- MBP-8» (Russia. 2006), correspondingly. Results/Discussion: It is revealed, that performance of techniques of different biomechanical parameters is determined by specific EMG patterns of the working muscles which parameters depend on coordination complexity of the performed motor action, subjects` sports qualifica-tion, as well as the character of counteraction of a rival, using counter-attacking and defensive techniques. Developing of muscle fatigue was accompanied by natural changes of duration of the tested technique (a «leg grip» throw), its kinematic parameters - speed, acceleration, movements of an athlete`s parts of the body, dynamics of angular parameters, and also specific electromyography signs - change of the sequence of working muscles involvement, duration and amplitude of their electric activity. The quantitative changes and direction of dynamics of kinematic and electromyography parameters depends on a kind of physical activity. The greatest changes of the parameters of a «leg grip» throw are registered under the influence of the muscle loading - a model of wrestling competitive activity. Conclusion: In the process of muscle fatigue development the efficiency of a performed technique is achieved by means of specific changes of its biomechanical parameters and those of electric activity of skeletal muscles.